Design and Implementation of SDN IP Based on Open Network Operating System and Border Gateway Protocol - I Putu Agus Eka Pratama (Indonesian Scientific Journal, 2021)
The development of computer network technology in the form of Software Defined Networking (SDN), provides many facilities for users to be able to develop network control applications, which can separate the data plane function from the control plane. The existence of this separation on routers and switches makes it easy for developers to centrally develop software and devices according to what is needed by users. However, there were obstacles to implementing SDN on IP networks in a short time. For this reason, it is necessary to implement SDN in stages by adding SDN to the existing IP network in the form of SDN IP, so that SDN can be connected and exchange routing information autonomously. This study focuses on the design and implementation of SDN IP using the Open Network Operating System (ONOS) on the Border Gateway Protocol (BGP). The results show that the design and implementation of SDN IP based on ONOS and BGP can be done well, where SDN can connect and exchange routing information with the Autonomous System (AS) native BGP-based network. Key word(s): Autonomous System (AS) Border Gateway Protocol (BGP) Open Network Operating System (ONOS) Software-Defined Networking (SDN) SDN IP